RATIONALITY BEHIND FAST ACTING DRUGS IN AYURVEDA - Verma, *Deepika; Dr, Rajnikant (International Journal of Ayurveda and Pharma Research, 2018)
Ayurveda like any other life sciences, has its integrity and potential to understand and determining the cure of rather potential serious and emergency conditions. There are numerous examples of such clinical success stories mentioned in our ancient texts ranging from various surgical and Para-surgical operations done by Acharya Sushruta during emergency, to the treatment of the patients who are nearby death due to intake of certain poisons incidentally or accidentally, or due to any other chronic medical illness such as fever, Rakta-pitta, Kshataj-kasa, Grahni, Ura-Kshtaja etc., due to excessive blood loss or to any Marmabhighata (injury to vital organs). All these require a highly skilled health care system which is beneficial not only for its preventing aspects but a curative one too and need of fast acting substances or procedures. Most of people who have certain experiences or knowledge of Ayurveda commonly say that Ayurvedic medicines or treatments are slower in action. Is it true ? if yes, why they are so? If not, then what is truth?